A Systematic Study of the Mechanism of Acacetin Against Sepsis Based on Network Pharmacology and Experimental Validation - Ouyang, Yuanshuo; Rong, Yi; Wang, Yanming; Guo, Yanli; Shan, Liya; Yu, Xiushi; Li, Li; Si, Junqiang; Li, Xinzhi; Ma, Ketao (Frontiers in Pharmacology, 2021)
No effective protective or therapeutic strategies are currently available for sepsis, a clinical syndrome. Acacetin, a natural flavonoid from vegetables, fruits, and herbs, has anti-oxidative and anti-inflammatory effects that may reduce sepsis. Like most flavonoids, acacetin has many sepsis biotargets but the molecular mechanism of its activity against sepsis remains unclear. We adopted a comprehensive approach combining network pharmacology, molecular docking and experimentation to reveal potential targets and pathways of acacetin against sepsis. Firstly, in vivo validation in mice showed that acacetin suppressed pathological damage and pro-inflammatory cytokine expression in LPS-induced ALI and FHF, and in vitro experiments further confirmed that acacetin attenuates LPS-induced M1 polarization. Then network pharmacology screening revealed EGFR, PTGS2, SRC and ESR1 as the top 4 over-lapping targets in a PPI network, and the acacetin-targets-GO-KEGG-sepsis network was visualized in Cytoscape 3.7.0, showing the involvement of connexin/gap junction binding with acacetin activity against sepsis. Finally, Molecular docking verified that acacetin can bind the active sites of the 4 targets predicted by network pharmacology, and we further confirmed that acacetin can significantly inhibit the up-regulation of p-src induced by LPS in vitro. We also confirmed that acacetin attenuates LPS-induced M1 polarization through Connexin43/NF-κB (P65) pathway in vitro experiments. Thus, the protective effect of acetin against sepsis through a multi-target, multi-pathway mechanism. Moreover, the network pharmacology strategy combined with in vivo and in vitro experiments may provide a powerful tool for exploring drug and disease mechanisms.